2002
DOI: 10.1152/ajpheart.00193.2002
|View full text |Cite
|
Sign up to set email alerts
|

A highly potent peptide analgesic that protects against ischemia-reperfusion-induced myocardial stunning

Abstract: We recently discovered an opioid peptide analgesic, 2′,6′-dimethyltyrosine (Dmt)-d-Arg-Phe-Lys-NH2([Dmt1]DALDA), that can protect against ischemia-induced myocardial stunning. In buffer-perfused hearts, 30-min global ischemia followed by reperfusion resulted in a significant increase in norepinephrine (NE) overflow immediately upon reperfusion and significant decline in contractile force (45%). Pretreatment with [Dmt1]DALDA before ischemia completely abolished myocardial stunning and significantly reduced NE o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…In contrast, SS-20, which has no antioxidant activity, was unable to protect the ischemic heart against reperfusion stunning. We had previously reported that SS-02 can prevent myocardial stunning even when administered only during reperfusion (42), consistent with antioxidation as the mechanism of action. The ability of SS-02 to prevent stunning has been confirmed in rats in vivo.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In contrast, SS-20, which has no antioxidant activity, was unable to protect the ischemic heart against reperfusion stunning. We had previously reported that SS-02 can prevent myocardial stunning even when administered only during reperfusion (42), consistent with antioxidation as the mechanism of action. The ability of SS-02 to prevent stunning has been confirmed in rats in vivo.…”
Section: Discussionsupporting
confidence: 75%
“…Ischemia-Reperfusion Studies-Details of the isolated perfused guinea pig heart model have been published previously (42). Isolated hearts were perfused continuously with either Krebs-Henseleit solution or Krebs-Henseleit solution containing various SS peptides and allowed to stabilize for 30 min.…”
Section: Measurement Of Antioxidant Properties Of Ss Peptides In Vitro-mentioning
confidence: 99%
“…These properties make the SS peptides highly effective in prevention and treatment of IR injury (311). The Tyr-containing SS peptides can significantly reduce reperfusion arrhythmias, myocardial contractile function, and infarct size after myocardial ischemia (54); attenuate infarct size after cerebral injury (254); reduce acute kidney injury after renal IR (346); protect skeletal muscles; and preserve normal cellular architecture after 3 h of hind limb ischemia (350). Most importantly, these SS peptides are effective even when administered on reperfusion and require no pretreatment.…”
Section: A Tppmentioning
confidence: 99%
“…SS31 belongs to a family of cell-permeable mitochondria-targeted peptide antioxidants (ss peptides) that was first reported to inhibit ROS production, mitochondrial depolarization, and (I/R)-induced myocardial stunning in early 2000s [14,15]. SS31 is a tetrapeptide with a dimethyltyrosine residue, which provides ROS scavenging activity [15].…”
Section: Introductionmentioning
confidence: 99%